Influencing factors and mechanism of tourists’ pro-environmental behavior – Empirical analysis of the CAC-MOA integration model - Tang, Haiyan; Ma, Yong; Ren, Jie (Frontiers in Psychology, 2022)
Tourism has been perceived as an environmentally friendly industry for a long term, but the negative impact of tourist irresponsible behavior on the environment cannot be ignored. Tourists' pro-environmental behavior is crucial to the destination's sustainable development. Taking stimulus-organism-response (SOR) theory as a framework, this study explores the factors and mechanisms influencing tourists' pro-environmental behaviors by integrating cognitive-affective-conative (CAC) theory and motivation-opportunity-ability (MOA) theory. Through the PLS-SEM analysis with 548 questionnaires, the driving mechanism of tourists' pro-environmental behavior was deeply explored. The results indicate that environmental knowledge, motivation, and opportunity have significantly positive effects on tourists’ pro-environmental behavior. Environmental knowledge, motivation, opportunity, and ability have significant effects on environmental self-identity and environmental commitment. Except for the ability, the other three factors respectively influence tourists' environmental behavior through environmental self-identity and environmental commitment.